2006
DOI: 10.1038/sj.leu.2404326
|View full text |Cite
|
Sign up to set email alerts
|

Loss of antibodies and response to (re-)vaccination in children after treatment for acute lymphocytic leukemia: a systematic review

Abstract: Intensified chemotherapy regimens resulting in improved survival of children with acute lymphocytic leukemia (ALL) lead to concerns about therapy-induced immune damage reflected by the loss of protection of previous immunizations and the efficacy of (re-)vaccination. The severity of secondary immunodeficiency, however, is not clear and knowledge is based on a limited number of studies. We performed a systematic review on literature concerning vaccination data of children with ALL published since 1980. Eight st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
72
2
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 47 publications
(72 reference statements)
10
72
2
8
Order By: Relevance
“…Optimal primary vaccination and high herd immunity in the developed countries may reduce infection rates in ALL patients but increased migration and international travel might reduce herd immunity [26].…”
Section: Post-chemotherapy Vaccination Recommendations For Allmentioning
confidence: 99%
“…Optimal primary vaccination and high herd immunity in the developed countries may reduce infection rates in ALL patients but increased migration and international travel might reduce herd immunity [26].…”
Section: Post-chemotherapy Vaccination Recommendations For Allmentioning
confidence: 99%
“…Most published studies find that serum antibody titers often fall below protective levels during therapy and recover to a variable extent following the completion of treatment [2][3][4][5][6][7][8]. Whether or not the fall in titers is synonymous with a lack of protection is debatable as is the depth of chemotherapy-induced immunosuppression [2,3,8,9].…”
mentioning
confidence: 99%
“…Whether or not the fall in titers is synonymous with a lack of protection is debatable as is the depth of chemotherapy-induced immunosuppression [2,3,8,9]. An extensive study of 100 patients, treated on BFM, NY I or II, or legacy Pediatric Oncology Group protocols [2] found that survivors were at significantly increased risk of having subprotective antibody titers when assessed 1 year after completion of therapy, but that there was no correlation between antibody titers and therapy received.…”
mentioning
confidence: 99%
See 2 more Smart Citations